Pengukuran Kualitas Website SIM Polije Berdasarkan Respon Pengguna - Erlangga Lesmana putra; Fitri Dwi Fadilah; Kevin Igor Ibnu Listanto; Megawati Putri Martinez; Rani Purbaningtyas (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to evaluate the quality of the SIM Polije website using the ISO 9126 framework. The evaluation covers six main characteristics such as functionality, reliability, usability, efficiency, maintainability, and portability. The research method involves descriptive statistical analysis with a questionnaire distributed to 25 respondents. Each indicator is assessed and classified into three answer options. Validity is tested through Pearson Product Moment correlation analysis, and reliability is measured with Cronbach Alpha using SPSS. The results of the software quality measurement show an average percentage of 86%, indicating that the SIM Polije website meets the ISO 9126 standard with the criteria of